2006
DOI: 10.1096/fj.05-5225fje
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial damage due to SOD1 deficiency in SH‐SY5Y neuroblastoma cells: a rationale for the redundancy of SOD1

Abstract: Superoxide dismutases (SODs) represent the first line of defense against oxidative stress, which is considered an essential factor in several neurodegenerative diseases and aging. We investigated the role of the copper,zinc superoxide dismutase (SOD1) in the maintenance of intracellular redox homeostasis by analyzing the early effects of SOD1 down-regulation in SH-SY5Y neuroblastoma cells. Through the use of small interference RNA, SOD1 was efficiently down-regulated at 48 h after transfection without any sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 46 publications
0
42
0
1
Order By: Relevance
“…All values obtained by QRT-PCR overlapped with the microarray data at the 95% confidence interval, validating the microarray data we have obtained for these five genes at all time points and mouse models. 2 …”
Section: Validation Of Microarray Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All values obtained by QRT-PCR overlapped with the microarray data at the 95% confidence interval, validating the microarray data we have obtained for these five genes at all time points and mouse models. 2 …”
Section: Validation Of Microarray Resultsmentioning
confidence: 99%
“…The Srxn1 transcript was increased 2.3-fold, and sulfiredoxin protein was increased Ͼ6-fold. Mt1 transcript was increased 4.5-fold and Mt2 transcript was increased 3.6-fold (Supplemental Table S1), but the Mt2 data did not reach the statistical cutoff (P Ͻ 0.0083 vs. P Ͻ 0.005); the protein levels of metallothionein 1 ϩ 2 are increased 4.5-fold (Mt1 and Mt2 have the same molecular 2 For an extensive comparison of microarray vs. "true" fold changes see Tables 2 and 3 Genes showing a significant difference of Ͼ1.5-fold when we compared untreated WT mice with either WT mice treated with diquat (DQ) or untreated Gpx1 Ϫ/Ϫ and Sod1 Ϫ/Ϫ mice are shown. Duplicates (by gene name or unigene ID) were removed.…”
Section: Confirmation Of Selected Transcripts At the Protein Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Some reports showed that ROS generation during mitochondria-dependent apoptosis occurs downstream of the release of mitochondrial proapoptotic factors to cytosol. 44 In many apoptosis models, however, ROS act as upstream signaling molecules that initiate cell death.…”
Section: Discussionmentioning
confidence: 99%
“…2c) have decreased activity of SOD2. Although the role of SOD2 appears to be intrinsic for cellular survival, cytoplasmic copper/zinc SOD (SOD1) is far more abundant in the cell, accounting for 90% of the total SOD activity (18,19). Thus, we tested the protein expression of SOD1 in GILT Ϫ/Ϫ and GILT WT fibroblast cell line and primary fibroblasts (Fig.…”
Section: Gilt-deficient Mouse Fibroblasts Show Increased Proliferatiomentioning
confidence: 99%